TRANSFORMASI SISTEM PENGUPAHAN BERBASIS SYARIAH SEBAGAI ALERNATIF MENCIPTAKAN IKLIM INVESTASI YANG KONDUSIF DI INDONESIA - Ferricha, Dian (Dinamika, 2013)
ABTRACTÂ Nowadays diregulation of invesment is esier than in the past.Â  But The economy grows constanly.Â  It indicated that the policy of goverment is not significant yet to invite investors in Indonesia.Â  It is caused by the labour wage sistem is not properly.Â  The labour wage sistem should be based on syariâah.Thus, we can share between labour, investors, and state in building new mutualism relationship and actualizing the welfare state.Â Kata Kunci: Sistem Pengupahan, Syariâah, Iklim Investasi